Factors affecting the adoption of integrated cloudbased e-health record in healthcare organizations: A case study of Jordan - Sulaiman H.; Magaireah A.I. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cloud computing; Environmental regulations; Environmental technology; Public policy; Adoption; EHR; Environmental contexts; Healthcare organizations; Organizational context; Technology readiness; TOE; Top management support; Health care